Implementation of Prudential Principles in the Use of Disinfectants as an Effort to Prevent Covid-19 Pandemic for Legal Protection of Ecosystems - Otih Handayani (Faculty of Law, Universitas Sebelas Maret, 2020)
The Covid-19 pandemic spreads almost all over the world, including Indonesia. The rapid spread of many fatalities resulted in the government using various means to overcome the pandemic, among others, with preventive efforts through massive disinfectant spraying. This research aims to lysis on applying the principle of prudence in the use of a disinfectant. This research is doctrinal/normative legal research with a statutory approach. Data is collected with literature studies, qualitatively analyzed. The results describe the use of large and inappropriate disinfectants that cause environmental pollution and adverse effects on public health. Environmental law analysis using Law No. 32 of 2009 and the regulations below can protect legal certainty and protect everyone's right to a good and healthy environment to protect the entire ecosystem.